2019
DOI: 10.1371/journal.pntd.0007346
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti (Aag2)-derived clonal mosquito cell lines reveal the effects of pre-existing persistent infection with the insect-specific bunyavirus Phasi Charoen-like virus on arbovirus replication

Abstract: BackgroundAedes aegypti is a vector mosquito of major public health importance, transmitting arthropod-borne viruses (arboviruses) such as chikungunya, dengue, yellow fever and Zika viruses. Wild mosquito populations are persistently infected at high prevalence with insect-specific viruses that do not replicate in vertebrate hosts. In experimental settings, acute infections with insect-specific viruses have been shown to modulate arbovirus infection and transmission in Ae. aegypti and other vector mosquitoes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 82 publications
(127 reference statements)
1
45
0
Order By: Relevance
“…Interestingly, we also observe sharp 3' ends and +1U biases for piRNAs generated from Phasi Charoen-like virus ( Figure S1), a negative sense RNA virus from the Phenuiviridae family that persistently infects Aag2 cells (38). These findings indicate that Zuc-like piRNA biogenesis targets diverse RNA viruses.…”
Section: Aedes Aegypti Pirnas Have Sharp 3' Endsmentioning
confidence: 70%
“…Interestingly, we also observe sharp 3' ends and +1U biases for piRNAs generated from Phasi Charoen-like virus ( Figure S1), a negative sense RNA virus from the Phenuiviridae family that persistently infects Aag2 cells (38). These findings indicate that Zuc-like piRNA biogenesis targets diverse RNA viruses.…”
Section: Aedes Aegypti Pirnas Have Sharp 3' Endsmentioning
confidence: 70%
“…However, the effects of these viruses on their host are very poorly understood. A recent study revealed that preexisting infection of Aag2 cells with PCLPV did not affect the infection and growth of the mosquito-borne viruses in genus Flavivirus, Alphavirus, and Rhabdovirus in cell culture (42). GMV is a recently described two-segmented, currently unclassified virus.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of these viruses on their host is very poorly understood. A recent study revealed that Aag2 cells with pre-existing infection with PCLPV do not affect the infection and growth of the mosquito-borne viruses in genus Flavivirus , Alphavirus and Rhabdovirus in cell culture [69]. GMV is a recently described two-segmented, currently unclassified virus.…”
Section: Discussionmentioning
confidence: 99%